Increased fruit production in Cipocereus minensis (Cactaceae) associated with termite nests (Isoptera: Termitidae) in Campo Rupestre (Brazilian altitude grassland) - Julya Pires Souza; Laura Simões de Ávila; Tiago Fernandes Carrijo; Carlos Victor Mendonça-Filho; Thiago Santos (PLoS ONE, 2025)
Cipocereus minensis (Cactaceae) is a columnar, shrubby cactus endemic to the Campo Rupestre (Brazilian altitude grassland), often found associated with termite nests (Blattaria: Isoptera). This study investigates, for the first time, the association between cacti and termites, exploring the potential influence of termite nests on cactus production and phenology. Specifically, we assessed whether cacti in termite nests exhibited (i) different phenological pattern; (ii) greater reproductive structures produced; (iii) higher buds to immature fruits conversion rate; (iv) different responses in productivity related to temperature and rainfall; and (v) the termite species inhabiting the nests. Weekly quantitative phenological monitoring was conducted on 62 cacti (31 growing on termite nests, and 31 on rocky substrate) over 94 weeks (2018–2020). Temperature and rainfall were measured, and termites identified. Circular statistics were used to assess phenology, while GLMMs tested the effects of temperature, rainfall and substrate on the production of reproductive structures. For both substrates, C. minensis flowered and fruited throughout the year, with two to three more pronounced peaks annually, mainly in the dry season. GLMMs indicated that substrate influenced how cacti responded to climate fluctuations, particularly temperature. Seven termite species were identified in 24 inhabited nests, with up to three species per nest, while seven nests were abandoned. Cacti associated with termite nests exhibited greater flower buds and fruit production, and were more affected by climate at the onset of the phenological cycle ( timing ). Termite nests may provide microclimatic regulation (temperature e moisture) and can promote nutrient cycling, acting as “fertility islands” in the nutrient-poor Campo Rupestre soil, suggesting that the cacti grown in this substrate have access to more resources, such as nutrients and moisture.